Paraneoplastic myelitis in a patient with non-hodgkin lymphoma - M. N. Guseynova; L. G. Zaslavskii; E. A. Skornyakova (Klinicist)
Objective: description of a clinical case of the development of longitudinally spread transverse myelitis in a young woman suffering from nonHodgkin’s lymphoma (follicular, 1 degree, IIIA stage, complete remission from February 2017). This is a rare, significant case in clinical practice for both residents and neurologists, and the case is under discussion. It requires certain scientific studies in the search for specific antionkoneural antibodies or a more detailed study of the already known. It is necessary to introduce these studies into laboratory practice in Russia, which would help to accelerate the diagnosis of paraneoplastic myelitis.Materials and methods. Patient B., 30 years old, has been suffering non-Hodgkin’s lymphoma since February 2016 (follicular, I degree, IIIA stage, complete remission from February 2017), receives infusions of Rituximab with a dose of 600 mg once in 2 months, the subacute developed pronounced lower spastic paraparesis. In November 2018, suddenly, against the background of complete well-being, weakness and numbness of the legs appeared. The patient asked for help at the Center for Multiple Sclerosis on 11.17.2018, then she was hospitalized and examined. Patient B. received a pulse therapy with methylprednisolone 1000 mg intravenously № 5. Discharged with positive dynamics with a diagnosis of Demyelinating CNS disease, unspecified. Acute protracted transverse myelitis (LETM), EDSS = 3.5 points. On December 13, due to the increase in spacity and leg weakness, she was urgently hospitalized in the neurological department of the Clinical Hospital.Results. After the completion of laboratory and instrumental examination, the condition was regardedby us as paraneoplastic myelitis. Relapse of lymphoma was ruled out. The treatment was carried out: pulse therapy with methylprednisolone, Plasmapheresis and intravenous administration of IgG (Privigen) with a distinct positive dynamics.Conclusion. This clinical observation allowed us to become more familiar with paraneoplastic syndromes and, in particular, with paraneoplastic myelitis. In the clinical situation previously described, we encountered a number of features: longitudinally extensive transverse myelitis developed without relapse of lymphoma, progressed rapidly, there was no response to treatment (glucocorticosteroids, plasmapheresis, Rituximab). All these signs and MRI data of the cervical and thoracic spine (a symmetric hyper-intensive signal from level CII to level ThXI, mainly involving the central spinal cord T2 MRI mode) testified in favor of the paraneoplastic etiology of longitudinally extensive transverse myelitis.